Avise quando chegar - Muriel Reis dos Santos Machado (2024)
To facilitate the reader’s understanding, an instruction guide usually presents its information in a didactic way, breaking down the main steps of a process. In this way, its images also become an item to be followed by the student, displaying visual commands. “Let me know when you get there” is a set of four publications that appropriates instructional materials associated with the teaching of visual arts, published in Brazil in different periods of its history. Using images obtained from these references, new paths are provided for the reader.